COVID‐19: Current and future challenges in spine care and education ‐ a worldwide study. Issue 4 (28th August 2020) - Nolte, Michael T.; Harada, Garrett K.; Louie, Philip K.; McCarthy, Michael H.; Sayari, Arash J.; Mallow, G. Michael; Siyaji, Zakariah; Germscheid, Niccole; Cheung, Jason PY; Neva, Marko H.; El‐Sharkawi, Mohammad; Valacco, Marcelo; et al.
Abstract: Background: The COVID‐19 pandemic has impacted spine care around the globe. Much uncertainty remains regarding the immediate and long‐term future of spine care and education in this COVID‐19 era. Study design: Cross‐sectional, international study of spine surgeons. Methods: A multi‐dimensional survey was distributed to spine surgeons around the world. A total of 73 questions were asked regarding demographics, COVID‐19 observations, personal impact, effect on education, adoption of telemedicine, and anticipated challenges moving forward. Multivariate analysis was performed to assess factors related to likelihood of future conference attendance, future online education, and changes in surgical indications. Results: A total of 902 spine surgeons from seven global regions completed the survey. Respondents reported a mean level of overall concern of 3.7 on a scale of one to five. 84.0% reported a decrease in clinical duties, and 67.0% reported a loss in personal income. The 82.5% reported being interested in continuing a high level of online education moving forward. Respondents who personally knew someone who tested positive for COVID‐19 were more likely to be unwilling to attend a medical conference 1 year from now (OR: 0.61, 95% CI: [0.39, 0.95], P = .029). The 20.0% reported they plan to pursue an increased degree of nonoperative measures prior to surgery 1 year from now, and respondents with a spouse at home (OR: 3.55, 95% CI: [1.14, 11.08], P = .029) or who spend a large percentage of their time teaching (OR: 1.45, 95% CI: [1.02, 2.07], P = .040) were more likely to adopt this practice. Conclusions: The COVID‐19 pandemic has had an adverse effect on surgeon teaching, clinical volume, and personal income. In the future, surgeons with family and those personally affected by COVID‐19 may be more willing to alter surgical indications and change education and conference plans. Anticipating these changes may help the spine community appropriately plan for future challenges. Abstract :